Enhancing food security while reducing environmental impacts: Life cycle assessment of cultivation-irrigation systems and yield gap closure in paddy fields - Abdullah Darzi-Naftchali; Markus Berger; Fereshteh Batoukhteh; Ali Motevali (Heliyon)
Enhancing food and water security is crucial, not only by preventing additional burdens on the environment but also by significantly mitigating existing environmental challenges. Dry direct-seeding of rice (DDSR) and yield gap (YG) reduction are effective in enhancing water productivity (WP) and food production. However, their related environmental impacts (EI) have received less attention. This study uses life cycle assessment and farmers' field data to analyze the EI of five rice cultivation-irrigation systems: transplanting with continuous flooding (T-CF), transplanting with alternate wetting and drying (T-AWD), DDSR with drip irrigation (DDSR-D), DDSR with sprinkler irrigation (DDSR-S), and DDSR with furrow irrigation (DDSR-F). Additionally, the energy productivity (EP) and WP of these systems were assessed. An environmental efficiency of YG reduction (EE) index was introduced as the ratio of EI reduction to YG reduction to evaluate the EI of closing YG. DDSR-D significantly reduced water, electricity, diesel fuel, and machinery use by 61–200 %, 14–64 %, 7–98 %, and 13–46 %, respectively. DDSR-D achieved the highest rice yield, which was 3.8 %, 4.4 %, 18.4 %, and 7.7 % higher than T-CF, T-AWD, DDSR-S, and DDSR-F, respectively. Compared with transplanting, DDSR increased EP and WP by 19.2 % and 63.8 %, respectively, and reduced CH4 and CO2 emissions by 26.5 % and 95.4 %, respectively. Overall, DDSR-D decreased the total EI by approximately 36.3 %, 13.3 %, 26.7 %, and 3.1 % compared to T-CF, T-AWD, DDSR-S, and DDSR-F, respectively. Sensitivity analysis indicated that EI was most impacted by electricity and diesel fuel consumption. Increasing the minimum yield by 80 %, 143 %, 205 %, 260 %, 310 %, and 322 % resulted in EI reductions of 77.8 %, 115.4 %, 159.2 %, 195.5 %, 209.6 %, and 193.4 %, respectively. The EE index was 0.36 Pt kg−1 for closing YG up to the average yield and 0.04 Pt kg−1 for closing YG from average to maximum yield, indicating that lower yields contribute more to environmental degradation. Based on the results, incorporating YG reduction strategies in DDSR-D can enhance the environmental sustainability of rice production and accelerate progress toward achieving sustainable development goals.